Writing extra : a resource book of multi-level skills activities - Palmer, Graham (Cambridge University Press, 2004)
Students are led step-by-step to a definite written outcome through a range of motivating activities such as role plays, discussions, games and text analysis. Each activity provides a meaningful context for real-world writing tasks such as writing e-mails, reports, letters, CVs and diaries. The book encourages students to look at the process of writing, thus developing their awareness of structure, content and their target audience.